Pengaruh Nilai Tukar, Ekspor, Inflasi, dan Suku Bunga terhadap Foreign Direct Investment di ASEAN - Rizalihadi, Firman Akbar; Andryan Setyadharma (ARBITRASE: Journal of Economics and Accounting, 2025)
Foreign Direct Investment (FDI) drives a country's economic development. Through increased productivity, FDI contributes to the economy, which can ultimately improve people's welfare. This study aims to analyze the relationship between exchange rate, export, inflation, and interest rate variables on FDI, partially and simultaneously, in four ASEAN countries, Indonesia, Malaysia, Singapore, and Vietnam, during 2014-2023. This study uses secondary data analyzed using the panel data regression method using the Fixed Effect Model (FEM) approach. The analysis results show that, partially, the exchange rate, inflation, and interest rate variables have a significant adverse effect on FDI. While the export variable has a significant positive effect on FDI. Simultaneously, the exchange rate, export, inflation, and interest rates affect FDI. Strategic policies are needed to increase the competitiveness of FDI in the four ASEAN countries studied. This policy includes stabilizing the exchange rate through interest rate control, increasing value-added exports, and maintaining price stability by the monetary authority so that inflation remains controlled.